KEWENANGAN CAMAT DALAM MENGKOORDINASIKAN PENYELENGGARAAN KETENTRAMAN DAN KETERTIBAN UMUM DI KECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI TAHUN 2018 - Wulandari, Adinda; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Authority is a power at government to doing the function and the duty based on regulation constibution. Subdistrict head is aleader as territory device at district or sub-district. Subdistrict head domiciled as a coordinator of organization government at sub dictrict area, his located at down and have a responsible to district head by region seccrtary district or city. With other word Authority is a power that have base to take action or dead of law so that not arise Iaw conseguence, that is materialized a authority.Formulation of the prolem in this research is â€œ why authority of sub-disrtict in coordinated effort the organization pece and public order at â€œLogas Tanah Daratâ€ sub-district not yet optimal? And aim of this research is to know the factor that couse peace and public order at Logas Tanah Drat sub-district. This research use Kualitative descriptive opproach.The resuts of this research is still the less coordination of doing sub-dictrict party, less communication of society to high party is cause of problem that happen notywt can to handled goodly because sub-district head not fully have the responsible. Often happen a changes of official make sub-district head cannot to geve permission to new arrivals society about establishment of worship house, very much the problem abandoned by sub-district so happen a less optimal of handled a problem.Keyword: Authority of sub-District Head, Peace and Public Order